Accuracy and reliability of GPS devices for measurement of sports-specific movement patterns related to cricket, tennis, and field-based team sports - Vickery, W. M.; Dascombe, B. J.; Baker, J. D.; Higham, D. G.; Spratford, W. A.; Duffield, R. (The Journal of Strength and Conditioning Research, 2014)
The aim of this study was to determine the accuracy and reliability of 5, 10, and 15 Hz global positioning system (GPS) devices. Two male subjects (mean ± SD; age, 25.5 ± 0.7 years; height, 1.75 ± 0.01 m; body mass, 74 ± 5.7 kg) completed 10 repetitions of drills replicating movements typical of tennis, cricket, and field-based (football) sports. All movements were completed wearing two 5 and 10 Hz MinimaxX and 2 GPS-Sports 15 Hz GPS devices in a specially designed harness. Criterion movement data for distance and speed were provided from a 22-camera VICON system sampling at 100 Hz. Accuracy was determined using 1-way analysis of variance with Tukey's post hoc tests. Interunit reliability was determined using intraclass correlation (ICC), and typical error was estimated as coefficient of variation (CV). Overall, for the majority of distance and speed measures, as measured using the 5, 10, and 15 Hz GPS devices, were not significantly different (p > 0.05) to the VICON data. Additionally, no improvements in the accuracy or reliability of GPS devices were observed with an increase in the sampling rate. However, the CV for the 5 and 15 Hz devices for distance and speed measures ranged between 3 and 33%, with increasing variability evident in higher speed zones. The majority of ICC measures possessed a low level of interunit reliability (r = -0.35 to 0.39). Based on these results, practitioners of these devices should be aware that measurements of distance and speed may be consistently underestimated, regardless of the movements performed